RNA profiling of circulating tumor cells systemically captured from diagnostic leukapheresis products in prostate cancer patients. (15th December 2022) - Dong, Liang; Du, Xinxing; Lu, Changxue; Zhang, Zhongyuan; Huang, Chung-Ying; Yang, Lei; Warren, Sarah; Kuczler, Morgan D.; Reyes, Diane K.; Luo, Jun; Amend, Sarah R.; Xue, Wei; et al.
Abstract: The application of circulating tumor cells (CTCs) in both clinical practice and research has been continuously limited by the rare number of targets that can be found in a tube of peripheral blood. Diagnostic leukapheresis (DLA) was used to increase the sampling volume. AdnaTest was used to process the whole leukopak, and the RNAs of captured CTCs was then profiled by NanoString nCounter platform. Spike-in experiments and leukopaks from patients with metastatic prostate cancer were used to validate this new strategy. The whole leukopak was further concentrated five times to reduce the total volume from 150 ​mL to 30 ​mL, which enabled it to be processed by 3 separate AdnaTest kits. The spike-in experiment demonstrated a reliable capture when there were more than 100 cancer cells/10 ​mL of concentrated leukopak. In 1 out of 5 real patient samples, CTCs were only detected in the leukopak, but not in peripheral blood. The RNA profiling of DLA CTCs indicated a more aggressive phenotype of CTCs occurred when the patient was experiencing a disease relapse, even when the serum prostate specific antigen (PSA) level was still relatively low and CTCs in peripheral blood were not detectable. We established a new protocol, integrating DLA, AdnaTest and NanoString nCounter technology, to profile RNAs from CTCs captured from a large blood screening volume. The new protocol can process the whole leukopak with sensitive CTC capture. The RNA profiling of CTCs can provide valuable information for disease monitoring. Graphical abstract: Image 1